Sticky knowledge : barriers to knowing in the firm - Szulanski, Gabriel (Sage strategy series., 2003)
Why don't best practices spread within firms? This book explains that the transfer of practices is a complex phenomenon, and demonstrates the range of barriers to transferring best practices within a firm.